U.S.N.S. Eltanin plotting chart / prepared by the American Geographical Society for the United States Antarctic Research Program of the National Science Foundation. - American Geographical Society of New York (New York : American Geographical Society of New York, 1965)
Sheet 1 South Pacific -- Sheet 2 South Pacific -- [Sheet adjoining sheet 2] -- Sheet 3 South Atlantic -- Sheet 4 Indian Ocean -- Sheet 5 Indian Ocean. Held at the American Geographical Society Library, University of Wisconsin Milwaukee. Grayscale; Scale 1:7,500,000 in latitude 71° Lambert conformal conic proj